2019
DOI: 10.1038/s41598-019-45213-z
|View full text |Cite
|
Sign up to set email alerts
|

Land use and land cover change effect on surface temperature over Eastern India

Abstract: Land use and land cover (LULC) change has been shown to have significant effect on climate through various pathways that modulate land surface temperature and rainfall. However, few studies have illustrated such a link over the Indian region using observations. Through a combination of ground, satellite remote sensing and reanalysis products, we investigate the recent changes to land surface temperature in the Eastern state of Odisha between 1981 and 2010 and assess its relation to LULC. Our analysis reveals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(82 citation statements)
references
References 58 publications
4
77
0
1
Order By: Relevance
“…This result has also been confirmed in many regional climate change studies 41,42 . The results of the correlation analysis also show that vegetation cover, air humidity, and distance from water bodies can significantly regulate surface temperature, which is similar to the findings of many studies on urban thermal environments [43][44][45][46] . Therefore, managers need to pay more attention to the protection of the ecological functions of wetlands and rice paddies and implement ecological restoration projects under the concept of the community of life of mountains, water, fields, lakes, grass and people.…”
Section: Discussionsupporting
confidence: 84%
“…This result has also been confirmed in many regional climate change studies 41,42 . The results of the correlation analysis also show that vegetation cover, air humidity, and distance from water bodies can significantly regulate surface temperature, which is similar to the findings of many studies on urban thermal environments [43][44][45][46] . Therefore, managers need to pay more attention to the protection of the ecological functions of wetlands and rice paddies and implement ecological restoration projects under the concept of the community of life of mountains, water, fields, lakes, grass and people.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, this study revealed that during the early 2000s, the rate of change of areal averaged temperature over entire urban centers was greater than the 1990s, with the mean, minimum, and maximum increased by 0.7, 1.3, and 0.3 o C, respectively. In East India, Partha et al (2019) documented that an increase in areal-averaged temperatures was associated with LULC changes of urbanization, and with spatio-temporal variation, up to half of the warming due to LULC change in urban centers. Similarly, over four urban centers in Southwest Ethiopia, LULCC could possibly be attributed to the areal-averaged observed minimum, maximum, and mean temperature change with the order of 0.32, 0.41, and 0.32 o C/decade, respectively (Tables 3, 6; Figure 7; Supplementary Figures 2-4).…”
Section: Impacts Of Urbanization On Lulcc and Local Climatementioning
confidence: 99%
“…& Technol. 28 (4): 1517 -1529 2020June-September) (Gogoi et al, 2019). We used 8 knots and placed 4 knots at the beginning of the year and the remaining 4 knots at the end of the year based on the seasons that are characteristic of tropical regions.…”
Section: Methodsmentioning
confidence: 99%